Genetic diversity within and among aecia of the wheat rust fungus Puccinia striiformis on the alternate host Berberis vulgaris. Issue 6 (June 2017) - Rodriguez-Algaba, Julian; Sørensen, Chris K.; Labouriau, Rodrigo; Justesen, Annemarie F.; Hovmøller, Mogens S.
Abstract: An isolate of the fungus Puccinia striiformis, causing yellow (stripe) rust on cereals and grasses, was selfed on the alternate (sexual) host, Berberis vulgaris . This enabled us to investigate genetic variability of progeny isolates within and among aecia. Nine aecial clusters each consisting of an aecium (single aecial cup) and nine clusters containing multiple aecial cups were selected from 18 B. vulgaris leaves. Aeciospores from each cluster were inoculated on susceptible wheat seedlings and 64 progeny isolates were recovered. Molecular genotyping using 37 simple sequence repeat markers confirmed the parental origin of all progeny isolates. Thirteen molecular markers, which were heterozygous in the parental isolate, were used to analyse genetic diversity within and among aecial cups. The 64 progeny isolates resulted in 22 unique recombinant multilocus genotypes and none of them were resampled in different aecial clusters. Isolates derived from a single cup were always of the same genotype whereas isolates originating from clusters containing up to nine aecial cups revealed one to three genotypes per cluster. These results implied that each aecium was the result of a successful fertilization in a corresponding pycnium and that an aecium consisted of genetically identical aeciospores probably multiplied via repetitive mitotic divisions. Furthermore, the results suggested that aecia within a cluster were the result of independent fertilization events often involving genetically different pycniospores. The application of molecular markers represented a major advance in comparison to previous studies depending on phenotypic responses on host plants. The study allowed significant conclusions about fundamental aspects of the biology and genetics of an important cereal rust fungus. Highlights: Genetic diversity within and among aecia of Puccinia striiformis is reported. Progeny isolates derived from an aecium were always of the same genotype. An aecium was the result of the fertilization of a pycnium by a single spore genotype. Progeny isolates derived from a cluster of aecia revealed single or multiple genotypes. Pycnial clusters were in some cases fertilized by genetically different pycniospores.